Migraine and sleep disorders: a systematic review - Tiseo, Cindy; Vacca, Alessandro; Felbush, Anton; Filimonova, Tamara; Gai, Annalisa; Glazyrina, Tatyana; Hubalek, Irina Anna; Marchenko, Yelena; Overeem, Lucas Hendrik; Piroso, Serena; Tkachev, Alexander; Martelletti, Paolo; et al. (Journal of headache and pain, 2020)
Migraine and sleep disorders are common and often burdensome chronic conditions with a high prevalence in the general population, and with considerable socio-economic impact and costs. The existence of a relationship between migraine and sleep disorders has been recognized from centuries by clinicians and epidemiological studies. Nevertheless, the exact nature of this association, the underlying mechanisms and interactions are complex and not completely understood. Recent biochemical and functional imaging studies identified central nervous system structures and neurotransmitters involved in the pathophysiology of migraine and also important for the regulation of normal sleep architecture, suggesting a possible causative role, in the pathogenesis of both disorders, of a dysregulation in these common nervous system pathways. This systematic review summarizes the existing data on migraine and sleep disorders with the aim to evaluate the existence of a causal relationship and to assess the presence of influencing factors. The identification of specific sleep disorders associated with migraine should induce clinicians to systematically assess their presence in migraine patients and to adopt combined treatment strategies.